2023
DOI: 10.3390/antiox12030745
|View full text |Cite
|
Sign up to set email alerts
|

Ginger (Zingiber officinale) Root Capsules Enhance Analgesic and Antioxidant Efficacy of Diclofenac Sodium in Experimental Acute Inflammation

Abstract: Our study aimed to evaluate the analgesic and antioxidant effects of ginger (Zingiber officinale) root capsule extract (GRCE) in addition to diclofenac (D) sodium treatment in carrageenan-induced acute inflammation (AI). Seven groups of eight Wistar-Bratislava white rats were included in the study. One group was the control (C), and AI was induced in the other six groups. The following treatments were applied: saline solution for C and AI groups, D for the AID group, GRCE for two groups and GRCE and D for anot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…The tissue levels of the biomarkers could also be of interest in the demonstration of efficacy as a preliminary step in translation toward investigations on humans. It might also be of interest to investigate the synergic effect of LO in combination with other natural compounds (e.g., curcumin [45][46][47], ginger [24], etc.) added to standard thrombosis treatment to minimize the side effects of standard medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tissue levels of the biomarkers could also be of interest in the demonstration of efficacy as a preliminary step in translation toward investigations on humans. It might also be of interest to investigate the synergic effect of LO in combination with other natural compounds (e.g., curcumin [45][46][47], ginger [24], etc.) added to standard thrombosis treatment to minimize the side effects of standard medications.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response is accompanied by increased vascular permeability, infiltration of leukocytes, and other inflammatory mediators. In addition, it is known to stimulate the release of inflammatory mediators such as histamine, trypsin, and cytokines [24,25].…”
Section: Methodsmentioning
confidence: 99%
“…As stated in the pamphlet, the capsules contain ginger (Zingiber officinale) (root extract) (guaranteed 12.5 mg (5%) gingerols). We had already reported the GRCE phytochemical analysis and toxicity evaluation in our previous paper [21]. The phytochemical analysis revealed that 10-gingerol (525.418 µg/mL), 6-gingerol (443.182 µg/mL), 8-gingerol (360.897 µg/mL), 6-shogaol (369.816 µg/mL), and 1-Dehydro-6-gingerdione (304.115 µg/mL) were the main compounds of GRCE [21].…”
Section: Chemicals and Drugsmentioning
confidence: 99%
“…We had already reported the GRCE phytochemical analysis and toxicity evaluation in our previous paper [21]. The phytochemical analysis revealed that 10-gingerol (525.418 µg/mL), 6-gingerol (443.182 µg/mL), 8-gingerol (360.897 µg/mL), 6-shogaol (369.816 µg/mL), and 1-Dehydro-6-gingerdione (304.115 µg/mL) were the main compounds of GRCE [21]. Injectable diclofenac sodium and saline solution (0.9%) were also purchased from a local pharmacy in Cluj-Napoca.…”
Section: Chemicals and Drugsmentioning
confidence: 99%
See 1 more Smart Citation